Pengaruh Ekstrak Daun Melinjo Terhadap Laju Korosi Pada Material Baja: - - Sutrisno . (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2023)
In the rapid development of industry and construction in the current era, iron is a material that is widely used as a material in construction activities around the world. However, iron has the disadvantage of being very susceptible to corrosion. Corrosion is a decrease in metal quality due to electrochemical reactions with the environment. One of the corrosion prevention measures taken against iron is the addition of corrosion inhibitors to inhibit the corrosion rate. Inhibitors from natural materials are an alternative as an environmentally friendly inhibitor. This study aims to determine the efficiency of using melinjo leaf extract inhibitor in inhibiting corrosion rate in 3% Nacl corrosive media. The method used is the mass loss method to see the value of the corrosion rate. This study uses ST 37 steel plate material with a size of 2x1.5x0.12 cm. The concentration variation of melinjo leaf extract is 0%, 3%, 6%, and 9% with a soaking time of 14 days. The results showed that the addition of melinjo leaf extract as an inhibitor can reduce the corrosion rate with the smallest corrosion rate of 0.0449 mmpy and the greatest inhibitor efficiency is at a concentration of 9% at 51.72%.